1984
DOI: 10.3109/00016358408993887
|View full text |Cite
|
Sign up to set email alerts
|

Retention of complete maxillary dentures related to soft tissue function

Abstract: The influence of free tongue, lip, and cheek function on the retention of complete maxillary dentures was investigated for five experienced denture wearers. Test dentures were designed with full palatal coverage and functionally determined filling in of the vestibular sulcus. The front teeth were arranged primarily to meet cosmetic demands--that is, anterior to the top of the residual alveolar ridge. Retention was measured as resistance to dislodgement-provoking loads applied vertically to the incisive edge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The development of reflexes, as the tongue is functioning, helps complete denture wearers to stabilize their dentures. A good example is the stabilizing role that the tongue plays during swallowing, as it presses the posterior part of the upper denture in place ( Orstavik & Floystrand, 1984; Rahn & Heartwell, 1993). Where the denture is ill‐fitting, badly constructed, or occluding with natural anteriors ( Zarb et al ., 1990 ), the tongue is called to compensate the lack of stability; this may result in modified function, development of habits, or alteration of reflexes ( Kessler, 1955; Renner, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The development of reflexes, as the tongue is functioning, helps complete denture wearers to stabilize their dentures. A good example is the stabilizing role that the tongue plays during swallowing, as it presses the posterior part of the upper denture in place ( Orstavik & Floystrand, 1984; Rahn & Heartwell, 1993). Where the denture is ill‐fitting, badly constructed, or occluding with natural anteriors ( Zarb et al ., 1990 ), the tongue is called to compensate the lack of stability; this may result in modified function, development of habits, or alteration of reflexes ( Kessler, 1955; Renner, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a good result with a conventional maxillary implant assisted overdenture, it is better to be extended to cover the palatal area together with good adaptation and good peripheral seal at the borders (13) . It was found that retention of the denture was affected by covering the maxillary tuberosity more than covering the palatal area (14) . Reduction of the palatal part of maxillary implant assisted overdenture might not affect the retention or stability of the overdenture but provide several benefits for the patient as, decrease gaging reflex, improve taste sensation, better phonetic, and positive effect on rate of salivary flow (15) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve a satisfying result with a conventional maxillary overdenture, the overdenture design relies on good support and anatomy of the hard palate, together with good adaptation and vestibular seal at the borders . It has been demonstrated that the tuberosity coverage by the denture is more important for retention than the coverage of the palate . Reduction of the palatal coverage offers several benefits for the patients, including an enhanced taste sensation, better control of the gag reflex, a positive effect on salivary flow rate, and even phonetic benefits .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It has been demonstrated that the tuberosity coverage by the denture is more important for retention than the coverage of the palate. 15 Reduction of the palatal coverage offers several benefits for the patients, including an enhanced taste sensation, better control of the gag reflex, a positive effect on salivary flow rate, and even phonetic benefits. 14,[16][17][18][19] However, reduction of the palatal coverage might negatively influence the overdenture retention.…”
Section: Introductionmentioning
confidence: 99%